2-Furoic piperazide derivatives as promising drug candidates of type 2 diabetes and Alzheimer's diseases: In vitro and in silico studies. (December 2018) - Abbasi, Muhammad Athar; Hassan, Mubashir; ur-Rehman, Aziz; Siddiqui, Sabahat Zahra; Hussain, Ghulam; Shah, Syed Adnan Ali; Ashraf, Muhammad; Shahid, Muhammad; Seo, Sung Yum
Graphical abstract: Highlights: Synthesis of multi-functional 2-furoic piperazide derivatives. Enzyme inhibitory studies against different enzymes. Computational studies to augment the in vitro results. Suitable therapeutic agents for type 2 diabetes and Alzheimer's disease. Mild hemolytic agents toward red blood cell membrane. Abstract: The heterocyclic compounds have been extensively reported for their bioactivity potential. The current research work reports the synthesis of some new multi-functional derivatives of 2-furoic piperazide (1 ; 1-(2-furoyl)piperazine). The synthesis was initiated by reacting the starting compound1 with 3, 5-dichloro-2-hydroxybenzenesulfonyl chloride (2 ) in a basic, polar and protic medium to obtain the parent sulfonamide3 which was then treated with different electrophiles, 4a–g, in a polar and aprotic medium to acquire the designed molecules, 5a –g . These convergent derivatives were evaluated for their inhibitory potential against α -glucosidase, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. Acarbose was used as a reference standard for α -glucosidase inhibition while eserine for AChE and BChE inhibition. Some of the synthesized compounds were identified as promising inhibitors of these three enzymes and their bioactivity potentials were also supported by molecular docking study. The most active compounds among the synthetic analogues might be helpful in drug discovery and development for the treatment of type 2 diabetes and Alzhiemer's diseases.